Changes towards stable good somatic condition and increased gonad investment of Norwegian spring-spawning herring (Clupea harengus) after 2005 are linked to extended feeding period - Homrum, Eydna í; Óskarsson, Guðmundur J.; Ono, Kotaro; Hølleland, Sondre; Slotte, Aril (Frontiers in Marine Science, 2022)
Norwegian spring spawning herring (Clupea harengus) migrate from spawning areas on the Norwegian shelf in February-March to feeding areas in the Norwegian Sea in April-August, returning to wintering areas in northern Norwegian waters from September onwards when feeding ceases. After around 2005 the Norwegian Sea has become warmer and here we address recent changes in migration, somatic condition and gonad development of herring related to these changes. Analyses were based on combined Norwegian, Icelandic and Faroese data on fishery ( 81% of total commercial catch) and biological parameters from an extensive material of individual fish (n = 310749) during the period 1994-2019. Fishery data demonstrated large-scale changes in herring distribution over the study period. This was further supported by spatiotemporal modelling of body growth, somatic condition, gonad development and concurrent centre of gravity changes of the sampled fish. After 2005 the population showed a clear tendency of being distributed farther south-westwards in the Norwegian Sea during feeding and returning to wintering areas later in the year. This tendency increased with age, and with body length and somatic condition within age groups. Moreover, the somatic condition increased for all age groups from the early 2000s towards stable high levels after 2005, mainly due to extra weight gained from extended feeding into the autumn. Length at age decreased continuously during 2003-2010 for all age groups, suggesting impact of density dependent limiting factors but also that the environmental shift may have led to immediate poorer feeding conditions early in the year. Hence, extra energy from extended autumn feeding was rather invested into gonad weights tending to increase over the study period. Mechanisms behind the observed changes are likely linked to spatial and seasonal changes in zooplankton abundance. Overall, zooplankton production possibilities along the frontal areas in the south-western part of the Norwegian Sea have likely increased after the general environmental shift. This also includes a change towards increased probabilities of an additional second generation of some copepods developing in warmer waters, facilitating a prolonged feeding period for herring.